First Thoughts on Implementing the Framework for Information Literacy - Trudi E. Jacobson; Craig Gibson (Communications in Information Literacy, 2015)
Following the action of the ACRL Board in February 2015 in accepting the Framework for Information Literacy for Higher Education as one of the "constellation of documents" that promote and guide information literacy instruction and program development, discussion in the library community continues about steps in implementing the Framework. The spectrum of possibilities for implementing the Framework encompasses both curricular and co-curricular settings within colleges and universities. At this early stage of implementing the Framework, we suggest five curricular and instructional structures that can be thought of as a continuum of deepened engagement with its core ideas. The second half of this article presents two examples that show possible ways to incorporate elements of the Framework: a redesigned single instruction session and a course that illustrates a hybrid model blending the unit-based assignments with a course redesign.